Increased pin diameter improves torsional stability in supracondylar humerus fractures: An experimental study. (April 2016) - Pradhan, Anupam; Hennrikus, William; Pace, Gregory; Armstrong, April; Lewis, Gregory
Abstract: Background: Pediatric supracondylar humerus fractures are the most common elbow fractures seen in children, and account for 16 % of all pediatric fractures. Closed reduction and percutaneous pin fixation is the current treatment technique of choice for displaced supracondylar fractures of the distal humerus in children. The purpose of this study was to determine whether pin diameter affects the torsional strength of supracondylar humerus fractures treated by closed reduction and pin fixation. Methods: Pediatric sawbone humeri simulating a Gartland type III fracture were utilized. Four different pin configurations were compared. Specimens were subjected to a torsional load producing internal rotation of the distal fragment. The stability provided by 1.25- and 1.6-mm pins was compared. Results: The amount of torque required to produce 15° and 25° of rotation was greater using larger diameter pins in all models tested. The two lateral and one medial large pin (1.6 mm) configuration required the highest amount of torque to produce both 15° and 25° of rotation. Conclusions: In a synthetic pediatric humerus model of supracondylar humerus fractures, larger diameter pins (1.6 mm) provided increased stability compared with small diameter pins (1.25 mm). Fixation using larger diameter pins created a stronger construct and improved the strength of fixation.